Dynamics of the ACE2–SARS‐CoV‐2/ SARS‐CoV spike protein interface reveal unique mechanisms (2020)
The coronavirus disease 2019 (COVID-19) pandemic, caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is a major public health concern.A handful of static structures now provide molecular insights into how SARS-CoV-2 and SARS-CoV interact with its host target, which is the angiotensin converting enzyme 2 (ACE2). Molecular recognition, binding and function are dynamic processes.To evaluate this, multiple 500 ns or 1 μs all-atom molecular dynamics simulations were performed to better understand the structural stability and interfacial interactions between the receptor binding domain of the spike (S) protein of SARS-CoV-2 and SARS-CoV bound toACE2. Several contacts were observed to form, break and reform in the interface during the simulations. Our results indicate that SARS-CoV-2 and SARS-CoV utilizes unique strategies to achieve stable binding toACE2. Several diferences were observed between the residues of SARS-CoV-2 and SARS-CoV that consistently interacted withACE2. Notably, a stable salt bridge between Lys417 of SARS-CoV-2 S protein andAsp30 ofACE2 as well as three stable hydrogen bonds betweenTyr449,Gln493 and Gln498 of SARS-CoV-2 andAsp38,Glu35 and Lys353 ofACE2 were observed, which were absent in the ACE2–SARS-CoV interface. Some previously reported residues, which were suggested to enhance the binding afnity of SARS-CoV-2, were not observed to form stable interactions in these simulations. Molecular mechanics-generalized Born surface area based free energy of binding was observed to be higher for SARS-CoV-2 in all simulations. Stable binding to the host receptor is crucial for virus entry. Therefore, special consideration should be given to these stable interactions while designing potential drugs and treatment modalities to target or disrupt this interface.